On forms and fictions: a critical biography of Steven Campbell (1953-2007) - Rice, Gráinne (The University of Edinburgh, 2020)
The thesis is a definitive critical biography of Scottish artist Steven Campbell (1953-2007) underpinned by extensive archival research, semi-structured interviews, and relevant critical and historical secondary sources. The aim of the research was to write the essential point of reference for this artist and in the process to contest a few existing narratives around Campbell’s work in relation to its critical framing. Sources about Campbell are limited largely to exhibition reviews, exhibition catalogues and one monograph: The Story So Far by Duncan Macmillan published in 1993, several years before Campbell’s premature death in 2007. The thesis follows a chronological structure through Campbell’s educational and exhibition histories, looking at critical reception and the various artworld contexts through which he moved. It addresses the critical framing of Campbell that aligned his work with key relevant terminology of Neo-Expressionism, New Image Glasgow, and the New Glasgow Boys phenomenon. The thesis is informed by the research undertaken to compile the first catalogue raisonné for this artist, presented here as Appendix One. The methodological approach is broadly art historical, including iconographic analysis of individual works, reflection on the relevant contexts Campbell worked within and is informed by Visual Culture analysis. The Introduction covers key terminology used in the thesis and includes an overview of social and economic contexts for Campbell’s work. The Literature Review includes a gazetteer of key sources by typology. It charts how popular and critical reception to Campbell evolved during his career with reference to relevant recent art historical analyses. The first chapter looks at the formative educational and social contexts from which Campbell emerged, considering the specifics of the foundations of his expanded practice in the Mixed Media studios and Drawing and Painting Department at Glasgow School of Art (GSA) from the late 1970s-1982. The second chapter explores his early works made whilst living in New York between 1982-1986 with reference to recent scholarship on the 1980s art market. It charts the various exhibitions and collectors that underpinned his very swift success in New York and considers the impact that his American success had in the UK. The third chapter follows Campbell’s return to Scotland and the institution patronage he enjoyed. The fourth chapter is a detailed analysis of his 1990 On Form and Fiction exhibition in Glasgow. The fifth chapter documents the period in the 1990s when Campbell was operating from the ‘margins’ of ‘fashionability’. (McKenzie, Farquhar and Transmission Gallery, 2000; Bracewell, 2002). It considers how Campbell maintained his practice through exhibition and commissions albeit less prolifically than the previous decade. The sixth and final chapter narrates how his work has been rediscovered and critically re-evaluated in the years leading up to his death through changing curatorial contexts and considers the change of critical framework when On Form and Fiction was restaged in Edinburgh in 2014. The conclusion also evaluates the work undertaken on the catalogue raisonné and considers areas for further postdoctoral research.
Keywords: Steven Campbell; Scottish art; Contemporary art; postmodern art; history of Art; biography